Objectives: 1. Be able to solve a system of equations by using the substitution method. 2. Be able to solve a system of equations by using the elimination method. Critical Vocabulary: System of Equations, Elimination Daily Warm Up: Solve the following system of equations by substitution -2x + 2y = 4 2x + y = 5 I. Elimination (Standard Form) Example 4: Solve the system of equations -2x + 2y = 4 2x + y = 5 3y = 9 3 3 y=3 2x + (3) = 5 - 3 -3 2x = 2 2 2 x=1 -2x + 2(3) = 4 -2x + 6 = 4 - 6 -6 -2x = -2 -2 -2 x=1 Solution: (1, 3) If two equations are in standard form a system can be solved by ELIMINATION instead of SUBSTITUTION. Since both x-terms are opposites of each other (-2x and +2x), you can just add the equations together to ELIMINATE the “x” Solve for “y” Substitute into ONE of the original equations Write your solution I. Elimination (Standard Form) Example 5: Solve the system of equations 3x + 5y = 25 -3x - 10y = 55 Since both x-terms are opposites of each other (-3x and +3x), you can just add the equations together to ELIMINATE the “x” -5y = 80 -5 -5 y = -16 Solve for “y” 3x + 5(-16) = 25 3x - 80 = 25 + 80 +80 3x = 105 3 3 x = 35 Solution: (35, -16) Substitute into ONE of the original equations Write your solution I. Elimination (Standard Form) Example 6: Solve the system of equations 3x - 4y = 7 2x - y = 3 Multiply By -4 3x - 4y = 7 -8x + 4y = -12 -5x = -5 -5 -5 x=1 -8(1) + 4y = -12 -8 + 4y = -12 +8 +8 4y = -4 4 4 y = -1 3(1) - 4y = 7 3 - 4y = 7 -3 -3 2(1) - y = 3 -4y = 4 -4 -4 -y = 1 -1 -1 y = -1 y = -1 Solution: (1, -1) 2-y=3 -2 -2 There or no opposites here to ELIMINATE, but if you multiply everything in equation 2 by negative four you will have a -4y and +4y. Substitute into ONE of the original equations I. Elimination (Standard Form) Example 7: Solve the system of equations -5x + 3y = 10 3x - 2y = -8 Multiply By 2 Multiply By 3 -10x + 6y = 20 9x - 6y = -24 -1x = -4 -1 -1 x=4 3(4) - 2y = -8 12 - 2y = -8 -12 -12 -2y = -20 -2 -2 y = 10 -5(4) + 3y = 10 9(4) - 6y = -24 -10(4) + 6y = 20 -20 + 3y = 10 +20 +20 3y = 30 3 3 36 - 6y = -24 -36 -36 -6y = -60 -6 -6 y = 10 y = 10 -40 + 6y = 20 +40 +40 6y = 60 -6 -6 y = 10 Solution: (4, 10) Standard 5.1 Solving Systems Homework #2 1. x + y = 4 x - y = -10 6. x = 3y + 30 3y + x = 12 2. x + 3y = 3 x + 6y = 3 7. y = x - 9 x + 8y = 0 3. 2x - 3y = 0 3x - 2y = 5 8. -x + 4y = -20 3x - 12y = 48 4. 2x + 6y = 4 3x - 7y = 6 9. 3x + 6y = 8 -6x + 3y = 2 5. -4x + y = -8 -12x + 3y = -24 10. 2x + 5y = 8 5x - 6y = -1